INTRODUKSI TEKNOLOGI TEPAT GUNA UNTUK PERBAIKAN PROSES PRODUKSI DAN PENGEMBANGAN USAHA JAMU HERBAL DI CV. ARBA’IN JAYA MANDIRI SURAKARTA - Muhtadi -; Andi Suhendi; Agus Triyono; Agus Ulinuha (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
IPTEKDA LIPI XVIII activities in 2015 was intended to improve the quality and capacity of production in SMEs CV. Arba'in Jaya Mandiri Surakarta, through the introduction of some technology included medicinal herb powder mixer machines, mixer machines for honey, and semi-manual capsule filling. While in the second phase, will be introduced vacuum evaporator machine and application software for the development marketing online of herbal medicinal and honey products Arba'in. The results had been achieved in the first phase of IPTEKDA LIPI 2015, ie an increased in productivity and efficiency of production procesing as well as improving the quality of herbal medicine production. The mixing process of herbal ingredients were more efficient with the capacity of mixing up to 25 kg / process, from only 3-5 kg / process before. The process of mixing herbs-based honey, had showed a more homogeneous mixing and faster. Through the introduction and applications of technology production procesing, it was hoped will provide multifier effect for SMEs, employment, supplier partners and the communities.Keywords : SMEs CV. Arba'in Jaya Mandiri Surakarta, the introduction of efficient technology, production process improvement, business development of herbal medicine